Aktivitas Fisik dalam Olahraga Taekwondo - Setiawan, Fathiyyah Rhamadania; Arief, Kania Luwindawati Ainur; Suhardi, Cindy Dwi Ananda; Fua’din, Ahmad (Indonesian Journal Publisher, 2023)
This journal explores the role of physical activity in the context of Taekwondo, a martial art originating from South Korea. With a name derived from the use of empty-hand and kicking techniques, Taekwondo has gained global popularity as a sport encompassing martial arts, competition, and physical endurance. The research employs a descriptive research method to provide a comprehensive overview of physical activity in Taekwondo without manipulating variables. The study delves into various kinesiological aspects such as muscle strength, flexibility, balance, and coordination, which constitute the primary focus of Taekwondo training. Additionally, the journal underscores the significance of modern technology, such as tools measuring kicking power and motion sensors, in analyzing and monitoring athletes' physical activity. Both internal and external factors, including age, fitness level, experience, training environment, equipment, and weather conditions, are also considered due to their significant impact on physical activity in Taekwondo. Overall, a profound understanding of this physical activity is not only relevant to athlete development but also holds broad implications in the context of public health, physical education, and sports development at large.